TRANSFORMASI TRADISI MERARIK DI TENGAH MODERNISASI MASYARAKAT PRAYA - Nabila Amalia; Lalu Muh Istiqlal; Zulkarnaen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The merariq tradition is one of the traditional marriage customs of the Sasak community that continues to be preserved as part of local cultural identity. However, modernization has brought various changes to its implementation and meaning. This study aims to analyze the transformation of the merariq tradition amid modernization in Praya society and identify the factors influencing these changes. This research employs a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving traditional leaders, religious leaders, local communities, couples who practiced merariq, and Sasak youth. The findings indicate that the merariq tradition has undergone transformations in terms of implementation procedures, social values, and cultural meanings. Factors influencing these transformations include educational advancement, technological and communication developments, religious understanding, socio-economic conditions, and globalization. Despite these changes, the merariq tradition remains preserved as a cultural identity of the Sasak community through adaptations to modern developments without losing its essential cultural values.